Acid-triggered echogenic nanoparticles for contrast-enhanced ultrasound imaging and therapy of acute liver failure. (December 2018) - Go, Yebin; Lee, Hanui; Jeong, Lipjeong; Sun, Semi; Hong, Eunmi; Jung, Eunkyeong; Ko, Changgon; Noh, Joungyoun; Park, Sanghun; Lee, Moungyoung; Song, Chulgyu; Lee, Dongwon
Abstract: There has been increasing interest in the development of pathological stimulus-activatable nanoplatforms with theranostic functions. Here, we report ketalized maltodextrin (KMD) nanoparticles which are able to deliver therapeutic and imaging functions to the acidic conditions simultaneously, as may be found in the site of inflammation. KMD was synthesized as a platform of the theranostic nanoparticles by conjugating acid-cleavable hydrophobic moieties to maltodextrin through carbonate bonds. KMD nanoparticles could undergo acid-triggered hydrolytic degradation to generate carbon dioxide (CO2 ) bubbles, amplifying the ultrasound signal. The potential of KMD nanoparticles as a drug carrier was evaluated using silymarin as a model drug. KMD nanoparticles displayed significantly enhanced ultrasound contrast at acidic pH and released drug payloads in acid-triggered manners. The translational potential of silymarin-loaded KMD (s-KMD) nanoparticles as ultrasound contrast agents and therapeutic agents was thoroughly evaluated using cell culture models and mouse models of acetaminophen (APAP)-induced acute liver failure. s-KMD nanoparticles exhibited significantly enhanced ultrasound contrast in the APAP-intoxicated liver and also remarkably suppressed the hepatic damages by inhibiting the expression of pro-inflammatory cytokines. These results suggest that KMD nanoparticles hold tremendous potential as theranostic agents for various inflammatory diseases. Graphical abstract: Image 1